The role of subjective knowledge and perceived trustworthiness in fair trade consumption for fashion and food products. Issue 1 (16th November 2020) - Eberhardt, Tim; Hubert, Marco; Lischka, Helena Maria; Hubert, Mirja; Lin, Zhibin
Abstract : Purpose: The purpose of this study is to examine how subjective knowledge about fair trade products and the perceived trustworthiness of information about fair trade goods influence purchase intention and reported purchase behaviour across two product categories, namely, fashion and food. Design/methodology/approach: Data were collected from an online survey with a sample of 1, 616 consumers in four European countries, namely, Germany, Italy, Austria and the UK. Findings: The results show that subjective knowledge moderates the positive relationship between intentions to purchase and reported purchase behaviour of fair trade products, however, the moderating role of perceived information trustworthiness was not significant. Furthermore, both the intention to purchase and reported purchase behaviour are significantly lower for fair trade fashion products than for fair trade food products. Practical implications: This paper shows how fair trade consumption behaviour is mainly influenced by subjective knowledge about fair trade products. It reveals existing differences in both the buying intentions and reported purchase behaviour in different European markets. Originality/value: This research broadens the understanding of consumers' fair trade consumption behaviour across two different product categories and four different countries, with a focus on the interaction effect of consumers' subjective knowledge and information trustworthiness.